Pengembangan E-Bahan Ajar Berbantuan Augmented Reality Pada Mata Pelajaran IPAS Materi Mengubah Bentuk Energi Untuk Meningkatkan Hasil Belajar Peserta Didik Sekolah Dasar - Lulus Wiji Lestari; Novi Setyasto (Postgraduate, University of Mataram, 2025)
This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of augmented reality (AR)-based e-learning materials to enhance student learning outcomes. Employing a Research and Development (R&D) approach using the Borg and Gall model, the study involved students from Podorejo 02 Elementary School. Feasibility was assessed through expert validation, which indicated the e-learning materials were